Style in Delivering Directive Illocutionary Act in Mission Impossible-Dead Reckoning Part 1 Movie - Ida Bagus Suharta Adi Wiguna; Putu Devi Maharani (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
The aim of this study is to identify and describe the types of directive illocutionary acts present in the movie Mission: Impossible - Dead Reckoning Part 1 and the styles used to deliver these acts through the characters' utterances. Data were gathered by watching the movie multiple times, keeping track of any statements that seemed to imply directing acts, cross-referencing with the transcript, and categorizing the statements that contained directive illocutionary acts. This study found and identified three types of directives; commands, requests, and suggestions based on Kreidler (1998) theory. These types were further categorized into various styles, such as direct and indirect speech, and into sentence types (declarative, interrogative, and imperative) according to Yule's (1996) theory. The analysis was conducted using a qualitative method, with 40 instances of data collected. The most frequent type was command (26 data), followed by suggestion (8 data), and request (6 data). The most common style observed was direct imperative (24 data), followed by direct declarative (7 data), and indirect interrogative (3 data).